USE OF INFORMATION AND COMMUNICATION TECHNOLLOGIES AND ITS OFICIAL BEGINING IN COLOMBIAN EDUCATION - Benavides B., Jorge E. (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper aims an approximation towards history of new Technologies of Information and Communication (NICT) inclusion into Colombia’s Goverment speech since the beginning of 80’s. Their objective was to determinate a way to implement information technology in the official channels for both archives and speech for state’s modernization policy this was concerning to social, economic and academical development during a neo liberal context that tended towards globalization. Research was based on main document sources that expressed motives and interests that originated a mainly theorical and speech introduction of technological development following a neo liberal state that was heading towards globalization. There was a remarkable result on this decade’s official policy that was determinated by a special presure for modernising Se encontró que la política oficial de estos comienzos estuvo determinada por la presión para la modernización del aparato estatal y la urgencia por la integración al mundo interconectado de inicios globalizantes, a través de la creación de diferentes entidades e instituciones administrativas oficiales encargadas de la introducción de las nuevas tecnologías de la información para la capacitación del recurso humano, especialmente en educación.